Cellulose-siloxane composite particles, method for producing the same, and cosmetic
Patent Information
- Application Number
- JP2022087689
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2042-05-30
AI Technical Summary
Conventional synthetic polymer fine particles used in cosmetics are non-biodegradable, pollute the environment, and adsorb chemical pollutants, posing risks to aquatic life and human health, while existing cellulose-based solutions require organic solvents for surface treatment.
Composite particles are formed by coating cellulose or cellulose derivatives with polyorganosilsesquioxane, achieved through hydrolysis and condensation of organotrialkoxysilane in the presence of alkali, resulting in a biodegradable and silicone-coated surface.
The composite particles provide improved sliding properties, soft texture, and water repellency, suitable for cosmetics, offering biodegradability and reducing environmental impact.
Smart Images

Figure 00000015_0000 
Figure 00000015_0001 
Figure 00000015_0002
Abstract
Description
[Technical Field]
[0001] The present invention relates to cellulose-siloxane composite particles, a method for producing the same, and a cosmetic. [Background technology]
[0002] Various polymeric microparticles have been proposed for various applications. For example, microparticles contained in cosmetics have various purposes. The purposes of containing microparticles in cosmetics include improving the spreadability of cosmetics, changing the texture, providing a wrinkle-blurring effect, and improving the slipperiness of foundations and other products.
[0003] In particular, highly spherical particles have an excellent feel to the touch, and their physical properties and shape can produce a light scattering (soft focus) effect. When such particles are used in foundations and other products, they can be expected to fill in and smooth out unevenness in the skin, and by scattering light in various directions, they can make wrinkles and other imperfections less noticeable (soft focus).
[0004] In order to achieve these purposes and effects of cosmetics, the microparticles incorporated into cosmetics must have a narrow particle size distribution and high sphericity. As such microparticles, microparticles made from synthetic polymers such as polyamides such as nylon 12, polymethyl methacrylate (PMMA), and polystyrene (PS) have been proposed.
[0005] However, these synthetic polymer particles have a specific gravity of less than 1 and are so small in diameter that they tend to float on water and cannot be removed at wastewater treatment facilities, so they can flow directly into rivers and then into the sea, resulting in the problem of ocean pollution caused by these synthetic polymer particles.
[0006] Furthermore, these synthetic polymer microparticles adsorb trace amounts of chemical pollutants in the environment. Because of this property, there are concerns that the particles that have adsorbed these chemical pollutants may be ingested by plankton and fish, which could have adverse effects on the human body, among other things.
[0007] Due to these concerns, attempts have been made to replace the synthetic polymer microparticles used in a variety of applications with biodegradable particles.
[0008] A typical example of biodegradable resin is cellulose. Cellulose has the advantage that it can be obtained from natural materials such as wood and cotton, which do not compete with food or feed. For this reason, the development of cellulose-containing microparticles is desired.
[0009] Furthermore, synthetic resin powders made primarily from silicone are used in many cosmetics, such as hair cosmetics, makeup cosmetics, and sunscreens, as an important ingredient for forming a uniform film on the surface of skin and hair to provide moisture and smoothness, and for imparting water repellency and water resistance. For example, Japanese Patent Laid-Open Publication No. 07-196815 (Patent Document 1) discloses silicone microparticles, which are said to have a soft feel, no aggregation, and excellent dispersibility. Therefore, they are suitable for incorporation into cosmetics, but the development of better resin powders is desired.
[0010] WO2020 / 188698 discloses that cellulose acetate particles are surface-treated with a lipophilicity-imparting agent containing a silicone-based component and then incorporated into a cosmetic composition. However, the lipophilicity-imparting agent is attached to the cellulose acetate particles by a wet processing method, which requires the use of organic solvents such as n-hexane. Therefore, there is a need for the development of more environmentally friendly aqueous composite particles. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 07-196815 [Patent Document 2] WO2020 / 188698 Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made in consideration of the above circumstances, and aims to provide microparticles that are biodegradable and have excellent tactile feel by coating biodegradable cellulose particles with silicone that imparts properties such as sliding properties and water repellency to form composite particles. [Means for solving the problem]
[0013] As a result of extensive research into achieving the above object, the present inventors have developed composite particles in which cellulose particles are coated with polyorganosilsesquioxane, thereby completing the present invention. That is, the present invention provides composite particles comprising particles of cellulose or a cellulose derivative and polyorganosilsesquioxane attached to the surfaces of the particles, wherein the polyorganosilsesquioxane is a polymer of organotrialkoxysilane in an amount of 3 to 80 parts by mass per 100 parts by mass of the particles, a method for producing the composite particles, and a cosmetic containing the composite particles. [Effects of the Invention]
[0014] When blended and used in cosmetics, the composite particles of the present invention can impart properties such as sliding properties, soft touch, water repellency, etc. to the cosmetics. Therefore, the composite particles of the present invention can be blended in many cosmetics such as hair cosmetics, makeup cosmetics, and sunscreens. [Brief explanation of the drawings]
[0015] [Figure 1] FIG. 1 is an electron microscope photograph of the surface of the composite particles obtained in Example 4. [Figure 2] FIG. 2 shows (a) an enlarged electron microscope photograph of the surface of the composite particle obtained in Example 4, and (b) an image in which an elemental mapping image of silicon and an elemental mapping image of carbon are superimposed. [Figure 3] FIG. 3 is an electron microscope photograph of the surface of the composite particle obtained in Comparative Example 5. DETAILED DESCRIPTION OF THE INVENTION
[0016] The present invention relates to composite particles comprising particles of cellulose or a cellulose derivative and polyorganosilsesquioxane attached to the surfaces of the particles, characterized in that the polyorganosilsesquioxane is a polymer of organotrialkoxysilane in an amount of 3 to 80 parts by mass, preferably 5 to 70 parts by mass, and more preferably 15 to 55 parts by mass, per 100 parts by mass of the particles. This will be explained in detail below.
[0017] (A) Particles of cellulose or cellulose derivatives Particles of cellulose or cellulose derivatives (hereinafter collectively referred to as cellulose particles) are particles containing cellulose. They may be particles of cellulose derivatives such as cellulose acetate and cellulose acetate propionate. The shape of the cellulose particles is not limited to spherical, but cellulose particles are usually spherical. In the present invention, spherical cellulose particles are also preferred.
[0018] The volume-average particle diameter of the cellulose particles is preferably 1 to 300 μm. It is more preferably 1 to 150 μm, and more preferably 1 to 50 μm. More specifically, the volume-average particle diameter may be 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, or 45 μm. The volume-average particle diameter of the cellulose particles is the particle diameter at 50% cumulative volume determined from data obtained by measurement using a laser diffraction particle size distribution analyzer (e.g., "SALD2100" manufactured by Shimadzu Corporation).
[0019] The cellulose particles or cellulose derivatives can be produced, for example, by suspending a cellulose acetate solution in water, in which cellulose acetate is dissolved in an organic solvent, to prepare a suspension in which cellulose acetate particles are dispersed in water, removing the organic solvent from the suspension, and saponifying the cellulose acetate particles so that the amount of acetic acid relative to the mass of cellulose is 0.5 ppm or less. After the cellulose acetate particles are saponified to form cellulose particles, the water may be removed by solid-liquid separation, and the cellulose particles may be dried.
[0020] Examples of commercially available cellulose particles that can be used include BELLOCIA (registered trademark, manufactured by Daicel Corporation, cellulose acetate), Viscopearl (registered trademark, manufactured by Rengo), and ART PEARL NC-400 and NC-800 (manufactured by Negami Chemical Industries, Ltd.).
[0021] (B) Organotrialkoxysilane The composite particles of the present invention are formed by adhering polyorganosilsesquioxane to the surface of the above-mentioned cellulose particles. The polyorganosilsesquioxane is a polymer of organotrialkoxysilane. The organotrialkoxysilane is represented by the following formula: R 1 Si(OR 2 )3 In the formula, R 1 is an alkyl group having 1 to 30 carbon atoms, and R 2 is hydrogen or an alkyl group having 1 to 4 carbon atoms, and is most preferably a methyl group. 1 represents an alkyl group having 1 to 30 carbon atoms, preferably 1 to 12 carbon atoms, and more preferably 1 to 8 carbon atoms. A methyl group is most preferred. The organotrialkoxysilane may be used alone or in combination of two or more types.
[0022] The organotrialkoxysilane is preferably methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, ethyltributoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, n-octyltriethoxysilane, n-octyltrimethoxysilane, i-octyltrimethoxysilane, It is i-octyltriethoxysilane.
[0023] The organotrialkoxysilanes are well known and commercially available, and are described, for example, in U.S. Patent No. 5,300,327 (April 5, 1994), U.S. Patent No. 5,695,551 (December 9, 1997), and U.S. Patent No. 5,919,296 (July 6, 1999).
[0024] As the organotrialkoxysilane, particularly preferred is R 1 and R 2 is methyltrimethoxysilane, where
[0025] [Manufacturing method] The present invention provides a method for producing composite particles comprising (A) cellulose or cellulose derivative particles and polyorganosilsesquioxane attached to the surfaces of the particles, the method comprising the steps of: subjecting 3 to 80 parts by mass of (B) organotrialkoxysilane per 100 parts by mass of the (A) particles to a hydrolysis and condensation reaction with the (A) particles and water in the presence of an alkali to form polyorganosilsesquioxane; and then attaching the polyorganosilsesquioxane to the surfaces of the (A) particles. The method then includes a step of removing water. The polyorganosilsesquioxane is RSiO 3 / 2 The production method of the present invention will be described in detail below.
[0026] In step (i) of the production method of the present invention, (A) cellulose particles, water, and an organotrialkoxysilane (B) are subjected to hydrolysis and condensation reactions in the presence of an alkali to form a polyorganosilsesquioxane. The polyorganosilsesquioxane obtained by the hydrolysis and condensation reactions can be obtained in a state where it is attached to the cellulose particles.
[0027] The alkali acts as a catalyst for the hydrolysis and condensation reaction of (B) the organotrialkoxysilane, or as a catalyst for the condensation reaction. The alkali may be used alone or in combination of two or more. The alkali may be added directly or as an alkaline aqueous solution. Furthermore, the alkali may be blended into the aqueous dispersion containing cellulose particles and water before the organotrialkoxysilane is added, or may be added after the organotrialkoxysilane is added.
[0028] The amount of alkali added is such that the pH of the aqueous dispersion containing cellulose particles and water is preferably in the range of 9.0 to 13.0, more preferably 9.5 to 12.5. If the pH is within the above range, the hydrolysis and condensation reactions of the organotrialkoxysilane can proceed sufficiently, and the resulting polyorganosilsesquioxane can be sufficiently attached to the surfaces of the cellulose particles.
[0029] The alkali is not particularly limited, and may be any alkali that promotes the hydrolysis and condensation reaction of (B) organotrialkoxysilane. Examples of alkalis that can be used include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and barium hydroxide; alkali metal carbonates such as potassium carbonate and sodium carbonate; ammonia; tetraalkylammonium hydroxides such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; and amines such as monomethylamine, dimethylamine, diethylamine, trimethylamine, triethanolamine, and ethylenediamine. Among these, ammonia is the most suitable because it can be easily removed by volatilization from the resulting cellulose particle powder. A commercially available aqueous ammonia solution can be used as the ammonia.
[0030] The amount of (B) organotrialkoxysilane added is such that the amount of polyorganosilsesquioxane is in the range of 3 to 80 parts by mass, preferably 5 to 70 parts by mass, and more preferably 15 to 55 parts by mass, per 100 parts by mass of (A) cellulose particles. If the amount of (B) organotrialkoxysilane is less than 1, the effect of the siloxane is not exhibited, and if the amount exceeds the upper limit, uncoated siloxane and agglomerated particles are formed on the cellulose particles. If the amount exceeds the upper limit, uncoated siloxane and agglomerated particles are formed on the cellulose particles, resulting in an unpleasant feel and a hard, granular feel when incorporated into cosmetics.
[0031] (B) The organotrialkoxysilane is preferably added under stirring using a conventional stirrer such as a propeller blade or flat blade stirrer.
[0032] Furthermore, for the purpose of controlling the adhesion of polyorganosilsesquioxane to the surfaces of cellulose particles, a surfactant or a water-soluble polymer may be added to the aqueous cellulose dispersion.
[0033] The surfactant to be added to the aqueous dispersion is not particularly limited, and examples thereof include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. Two or more types of surfactants may be added. When a surfactant is added, the amount thereof is preferably in the range of 0.01 to 10 parts by mass per 100 parts by mass of the (A) cellulose particles.
[0034] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyethylene glycol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbit fatty acid esters, glycerin fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyglycerin fatty acid esters, propylene glycol fatty acid esters, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyoxyethylene fatty acid amides, polyoxyethylene-modified organopolysiloxanes, and polyoxyethylene polyoxypropylene-modified organopolysiloxanes.
[0035] Examples of anionic surfactants include alkyl sulfate salts, polyoxyethylene alkyl ether sulfate salts, polyoxyethylene alkylphenyl ether sulfate salts, sulfate salts of fatty acid alkylolamides, alkylbenzenesulfonates, α-sulfofatty acid ester salts, alkylnaphthalenesulfonic acids, alkyldiphenylether disulfosuccinates, fatty acid salts, polyoxyethylene alkyl ether carboxylate salts, N-acylamino acid salts, monoalkyl phosphate salts, dialkyl phosphate salts, and polyoxyethylene alkyl ether phosphate salts.
[0036] Examples of cationic surfactants include alkyltrimethylammonium salts, dialkyldimethylammonium salts, polyoxyethylenealkyldimethylammonium salts, dipolyoxyethylenealkylmethylammonium salts, tripolyoxyethylenealkylammonium salts, alkylbenzyldimethylammonium salts, alkylpyridium salts, monoalkylamine salts, and monoalkylamidoamine salts.
[0037] Examples of the amphoteric surfactant include alkyldimethylamine oxide, alkyldimethylcarboxybetaine, alkylamidopropyldimethylcarboxybetaine, alkylhydroxysulfobetaine, and alkylcarboxymethylhydroxyethylimidazolinium betaine.
[0038] The water-soluble polymer to be added to the aqueous dispersion is not particularly limited, and examples thereof include nonionic water-soluble polymers, anionic water-soluble polymers, cationic water-soluble polymers, and zwitterionic water-soluble polymers. The water-soluble polymers can be used alone or in combination of two or more. When a water-soluble polymer is added, the amount thereof is preferably in the range of 0.01 to 10 parts by mass per 100 parts by mass of the (A) cellulose particles.
[0039] Examples of nonionic water-soluble polymers include copolymers of vinyl alcohol and vinyl acetate, acrylamide polymers, vinylpyrrolidone polymers, copolymers of vinylpyrrolidone and vinyl acetate, polyethylene glycol, isopropylacrylamide polymers, methyl vinyl ether polymers, starch, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, guar gum, and xanthan gum.
[0040] Examples of anionic water-soluble polymers include dimethyldiallylammonium chloride polymers, vinylimidazoline polymers, methylvinylimidazolium chloride polymers, ethyl acrylate trimethylammonium chloride polymers, ethyl methacrylate trimethylammonium chloride polymers, acrylamidopropyl trimethylammonium chloride polymers, methacrylamidopropyl trimethylammonium chloride polymers, epichlorohydrin / dimethylamine polymers, ethyleneimine polymers, quaternized ethyleneimine polymers, allylamine hydrochloride polymers, polylysine, cationic starch, cationized cellulose, chitosan, and derivatives thereof copolymerized with monomers having a nonionic group or an anionic group.
[0041] Examples of amphoteric water-soluble polymers include copolymers of ethyltrimethylammonium chloride acrylate, acrylic acid, and acrylamide, copolymers of ethyltrimethylammonium chloride methacrylate, acrylic acid, and acrylamide, and Hoffmann degradation products of acrylamide polymers.
[0042] In one embodiment of the manufacturing method of the present invention, an alkali is blended with an aqueous dispersion containing cellulose particles and water (A), and then an organotrialkoxysilane (B) is added. In this case, the organotrialkoxysilane may be added all at once, but it is preferable to add it gradually over time. The reaction temperature when adding the organotrialkoxysilane is preferably 0 to 60°C, more preferably 0 to 40°C. A temperature within this range ensures successful adhesion of polyorganosilsesquioxane to the surface of the cellulose particles. After adding the organotrialkoxysilane, stirring is continued until the hydrolysis and condensation reactions of the organotrialkoxysilane are complete. To complete the hydrolysis and condensation reactions, the reaction may be carried out at room temperature or under heating at approximately 40 to 100°C, and alkali may be added as needed.
[0043] In another embodiment of the production method of the present invention, the organotrialkoxysilane may be added before the addition of the alkali. In this case, it is preferable to first add the organotrialkoxysilane to water. The organotrialkoxysilane may be added to water all at once or gradually over time. Alternatively, water may be added to the organotrialkoxysilane, or water and organotrialkoxysilane may be simultaneously placed in a tank and mixed. The temperature at which the organotrialkoxysilane is added to water is not particularly limited, and may be within the range of 0 to 100°C, for example. Thereafter, stirring is continued until the hydrolysis reaction of the organotrialkoxysilane progresses and at least the organotrialkoxysilane is dissolved in the water. At this time, a small amount of acid may be added to promote the hydrolysis reaction.
[0044] Then, an aqueous dispersion containing cellulose particles is added to the solution obtained above, followed by the addition of alkali. The addition of alkali causes a condensation reaction of the organotrialkoxysilane hydrolysate to produce polyorganosilsesquioxane. However, stirring must be stopped before polyorganosilsesquioxane is produced, or the stirring must be very slow. If the reaction solution flows at high speed during polyorganosilsesquioxane production, the polyorganosilsesquioxane will not adhere well to the cellulose particles.
[0045] The temperature during the condensation reaction is preferably 0 to 60°C, more preferably 0 to 40°C. When the temperature is within this range, polyorganosilsesquioxane can be successfully attached to the cellulose particles. The reaction solution is preferably left to stand or stirred very slowly until polyorganosilsesquioxane is produced (the polyorganosilsesquioxane is attached to the surface of the cellulose particles). The standing time is preferably in the range of 10 minutes to 24 hours. After that, to complete the condensation reaction, additional alkali may be added or the mixture may be heated to 40 to 100°C. Furthermore, normal stirring may be further performed.
[0046] In the step (ii) of the production method of the present invention, after polyorganosilsesquioxane is attached to the surface of the cellulose particles, water is removed by evaporation.
[0047] The water can be removed by evaporation by heating under normal pressure or reduced pressure. For example, the water can be removed by leaving the dispersion to stand under heating. As a pretreatment for this operation, the dispersion may be concentrated by filtration, centrifugation, decantation, or the like, and if necessary, the dispersion may be washed with water or a water-soluble alcohol.
[0048] If the powder of composite particles obtained by removing water by evaporation is agglomerated, it may be pulverized using a pulverizer such as a jet mill, a ball mill, or a hammer mill.
[0049] The composite particles obtained by the above method have cellulose particles coated with polyorganosilsesquioxane. The coating with polyorganosilsesquioxane can be confirmed by infrared absorption spectroscopy. Furthermore, the coating state can be confirmed by observing the surface in an electron microscope photograph. In particular, it is preferable that 30% or more, preferably 30% to 95%, more preferably 40% to 90%, and even more preferably 40% to 80% of the cellulose particle surface area be coated with polyorganosilsesquioxane. If the surface coverage of the cellulose particles is less than 30%, the effect of the siloxane is not exhibited. If the coverage is too high, uncoated siloxane or aggregated particles may form on the cellulose particles, resulting in a poor feel and the expected biodegradability of the cellulose particles. The volume-average particle diameter of the composite particles is preferably 1 to 300 μm. Furthermore, 1 to 150 μm is preferable, and 1 to 50 μm is even more preferable.
[0050] The static and dynamic friction coefficient of the composite particles is preferably 0.4 or less, which means that the composite particles have good smoothness and slipperiness. When blended and used in cosmetics as described below, the same effects can be imparted to the cosmetics. Note that the "composite particles" is formed by uniformly spreading the composite particles on a substrate such as a bioskin plate.
[0051] The composite particles of the present invention can be blended into cosmetics for use, and the blending amount of the composite particles relative to the total cosmetic is preferably 1 to 50% by mass, and more preferably 1 to 30% by mass. If the blending amount is less than the lower limit, sufficient effects may not be obtained. If the blending amount is more than the upper limit, undesirably, whiteness may become noticeable.
[0052] Examples of cosmetic ingredients other than the composite particulates of the present invention include oils, solvents, and powders other than silicone copolymer resin powders.
[0053] Examples of oils include hydrocarbons, silicone oils, triglycerides, ester oils, fats and oils, waxes, higher fatty acids having 12 to 20 carbon atoms, and higher alcohols having 8 to 20 carbon atoms, with low-boiling silicone oils, low-boiling isoparaffin hydrocarbons, triglycerides, and ester oils being particularly preferred. Examples of low-boiling silicone oils include octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and tetradecamethylcyclohexasiloxane. Examples of ester oils include fatty acid esters having 6 to 20 carbon atoms and glycerin fatty acid esters.
[0054] The content of the oil in the cosmetic varies depending on the formulation of the cosmetic, but may be any amount that does not impair the effects of the present invention. Preferably, it is 0.1 to 95% by mass, more preferably 1 to 80% by mass, based on the total of the powder and the resin powder component of the present invention. If the content is less than the lower limit, the effects of the oil, such as lubricity and moisturizing properties, may not be exhibited. If the content exceeds the upper limit, storage stability tends to decrease.
[0055] Examples of the solvent include medium- and lower-chain alcohols and aromatic alcohols, with lower alcohols having 1 to 4 carbon atoms, such as isopropyl alcohol, being preferred. The content of the solvent in the cosmetic of the present invention varies depending on the formulation of the cosmetic, and may be any amount that does not impair the effects of the present invention, but is preferably 0.1 to 80% by mass, and more preferably 1 to 50% by mass, of the total of the powder and the resin powder component of the present invention.
[0056] The powder refers to a material that can be used in ordinary (make-up) cosmetics, and is not particularly limited. It usually has an average particle size of 0.1 to 50 μm, and examples thereof include colorants such as inorganic color pigments, inorganic white pigments, and organic pigments, pearlescent agents, extender pigments, and organic powders.
[0057] Examples of powders include titanium oxide, zirconium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, mica, kaolin, sericite, muscovite, synthetic mica, phlogopite, lepidolite, biotite, lithia mica, silicic acid, anhydrous silicic acid, aluminum silicate, sodium silicate, sodium magnesium silicate, magnesium silicate, aluminum magnesium silicate, calcium silicate, barium silicate, strontium silicate, metal tungstate, hydroxyapatite, vermiculite, higilite, bentonite, montmorillonite, hectorite, zeolite, ceramic powder, dibasic calcium phosphate, alumina, aluminum hydroxide, phosphite, and the like. Uranium, boron nitride, etc.; organic powders such as polyamide powder, polyester powder, polyethylene powder, polypropylene powder, polystyrene powder, polyurethane powder, benzoguanamine powder, polymethylbenzoguanamine powder, polytetrafluoroethylene powder, polymethyl methacrylate powder, cellulose, silk powder, nylon powder, 1,2-nylon, 6-nylon, silicone powder, polymethylsilsesquioxane spherical powder, styrene-acrylic acid copolymer, divinylbenzene-styrene copolymer, vinyl resin, urea resin, phenolic resin, fluororesin, silicon resin, acrylic resin, melamine resin, epoxy resin, polycarbonate resin, microcrystalline fiber powder, starch powder, lauroyl lysine, etc.; surfactant metal salt powders such as zinc stearate, aluminum stearate, calcium stearate, magnesium stearate, zinc myristate, magnesium myristate, zinc palmitate, zinc laurate, zinc cetyl phosphate, calcium cetyl phosphate, and zinc cetyl phosphate sodium;Examples of colored pigments include inorganic red pigments such as red iron oxide, iron oxide, iron hydroxide, and iron titanate, inorganic brown pigments such as γ-iron oxide, inorganic yellow pigments such as yellow iron oxide and ochre, inorganic black pigments such as black iron oxide and carbon black, inorganic purple pigments such as manganese violet and cobalt violet, inorganic green pigments such as chromium hydroxide, chromium oxide, cobalt oxide, and cobalt titanate, inorganic blue pigments such as Prussian blue and ultramarine, Red No. 3, Red No. 104, Red No. 106, Red No. 201, Red No. 202, Red No. 204, Red No. 205, Red No. 220, Red No. 226, Red No. 227, Red No. 228, Red No. 230, Red No. 401, Red No. 505, Yellow No. 4, Yellow No. 5, Yellow 202, Yellow 203, and Yellow 2. Examples of pigments include lakes of tar-based pigments such as Yellow 401, Blue 1, Blue 2, Blue 201, Blue 404, Green 3, Green 201, Green 204, Green 205, Orange 201, Orange 203, Orange 204, Orange 206, and Orange 207, and lakes of natural pigments such as carminic acid, laccaic acid, carthamine, brazilian, and crocin. Pearl pigments include titanium dioxide-coated mica, titanium mica, iron oxide-treated titanium mica, bismuth oxychloride, titanium dioxide-coated bismuth oxychloride, titanium dioxide-coated talc, fish scale foil, and titanium dioxide-coated colored mica. Examples of metal powder pigments include aluminum, gold, silver, copper, platinum, and stainless steel powder.
[0058] Furthermore, in addition to the above-mentioned components, the cosmetic of the present invention can contain other components that are typically incorporated into cosmetics, such as surfactants, oily components, polymeric compounds, gelling agents, alkaline agents, polyhydric alcohols, pH adjusters, UV absorbers, antioxidants, preservatives, anti-inflammatory agents, skin-beautifying components, and fragrances, within quantitative and qualitative ranges that do not impair the effects of the composite particles of the present invention, depending on the purpose.
[0059] Examples of cosmetics of the present invention include makeup cosmetics such as foundation, face powder, eye shadow, eye liner, eyebrow pencil, blush, lipstick, nail color, etc., basic cosmetics such as emulsions, creams, lotions, calamine lotions, sunscreens, tanning agents, aftershave lotions, pre-shave lotions, packs, acne cosmetics, essences, etc., hair cosmetics such as shampoos, rinses, conditioners, hair colors, hair tonics, setting agents, hair care products, permanent agents, etc., body powders, deodorants, depilatories, soaps, body shampoos, bath additives, hand soaps, perfumes, etc. The silicone copolymer resin powder of the present invention is preferably used in powder cosmetics such as foundation, face powder, eye shadow, eyebrow pencil, etc. [Example]
[0060] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, parts and % represent parts by mass and % by mass, respectively.
[0061] [Example 1] A 500 ml reactor was charged with 100 parts by weight of spherical cellulose particles (A-1) with an average particle size of 7 μm, 830 parts by weight of ion-exchanged water, and 1.6 parts by weight of dodecyltrimethylammonium chloride (cationic BB, a cationic emulsifier manufactured by NOF Corp.) and stirred for 30 minutes. 22 parts by weight of 25% aqueous ammonia was added, and the pH was adjusted to 11-12 (using a benchtop pH meter HM-42X manufactured by Toa DKK Corporation). After cooling to 5°C, 22.5 parts by weight of methyltrimethoxysilane (KBM13, manufactured by Shin-Etsu Chemical Co., Ltd.) was added over 20 minutes. The mixture was then aged for 1 hour at 8°C, heated to 55°C, and 53 parts by weight of 25% aqueous ammonia was added and aged for 1 hour to obtain a slurry. The slurry was subjected to suction filtration for solid-liquid separation and allowed to dry, yielding a monodisperse, water-repellent powder. Electron microscopy confirmed that the mixture was composed of composite particles with polymethylsilsesquioxane attached to the surface of the granular cellulose particles.
[0062] [Example 2] The steps of Example 1 were repeated except that 15 parts by mass of methyltrimethoxysilane was used to obtain a monodisperse, water-repellent powder. Electron microscopy confirmed that the powder was a composite particle in which polymethylsilsesquioxane was attached to the surface of granular cellulose particles.
[0063] [Example 3] The steps of Example 1 were repeated except that 55 parts by mass of methyltrimethoxysilane was used to obtain a monodisperse, water-repellent powder. Electron microscopy confirmed that the powder was a composite particle in which polymethylsilsesquioxane was attached to the surface of granular cellulose particles.
[0064] [Example 4] The steps of Example 1 were repeated except that the spherical cellulose particles with an average particle size of 7 μm were replaced with spherical cellulose particles (A-2) with an average particle size of 15 μm and the amount of methyltrimethoxysilane was changed to 40 parts by mass, thereby obtaining a monodisperse, water-repellent powder. When these composite particles were observed under an electron microscope, particles with a particle size of approximately 100 nm were confirmed on the particle surface. Furthermore, when the infrared absorption spectrum was measured using an FT-IR measurement device (manufactured by Shimadzu Corporation) using the potassium bromide tablet method, the wave number was 2960 cm -1 , 1260cm -1 , and 1100-1020cm -1 Characteristic absorption was observed in the cellulose granules. This confirmed that the particles were composite particles in which polymethylsilsesquioxane was attached to the surface of granular cellulose particles. Figure 1 shows an electron microscope photograph of the surface of the composite particles. Figure 2 shows an electron microscope photograph (a) of the surface of the composite particles and a corresponding image (b) superimposed on the elemental mapping image of silicon and elemental mapping image of carbon analyzed with a SwiftED3000 (Hitachi).
[0065] [Example 5] Composite particles were obtained by repeating the steps of Example 1, except that the spherical cellulose particles having an average particle size of 7 μm were replaced with spherical cellulose particles (A-2) having an average particle size of 15 μm and the amount of methyltrimethoxysilane was changed to 15 parts by mass.
[0066] [Example 6] Composite particles were obtained by repeating the steps of Example 1, except that the cellulose particles of Example 1 were replaced with spherical cellulose particles (A-3) having an average particle size of 5 μm.
[0067] [Comparative Examples 1 to 3] The cellulose particles (A-1), (A-2), and (A-3) were subjected to evaluation without being treated with methyltrimethoxysilane.
[0068] In Comparative Example 4, a silane resin powder (average particle size 5 μm, X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd., B-2) was evaluated.
[0069] Comparative Example 5 Composite particles were obtained by repeating the steps of Example 1 except that the amount of methyltrimethoxysilane was changed to the amount shown in Table 2. An image of the particle surface of Comparative Example 5 is shown in FIG.
[0070] The composite particles obtained above were evaluated as follows, and the results are shown in Tables 1 and 2.
[0071] <Coverage rate> The average coverage' was calculated visually from electron microscope photographs of the surfaces of 10 composite particles. Coverage rate = Coverage area / Surface area x 100 It was calculated as:
[0072] <Method for measuring touch and stretchability> An appropriate amount of the powder sample was applied to a finger, which was then placed on black carbon paper and slid across the paper in one go. The sensation felt when slid was the tactile sensation, and the length of the trace left was the extensibility, which was evaluated using the following three levels. ○: Has a unique, smooth feel △: Slightly smooth feeling ×: Resistance is felt to the fingers and there is no slippery feeling
[0073] <Method for measuring friction coefficient> Approximately 1 g of the powder sample was evenly spread on a Bioskin plate (Beaulax) to create a sample piece containing a composite made of composite particles. A HEIDON TYPE-38 (Shinto Scientific) indenter with a 100 g weight was placed in vertical contact with the composite of the sample piece, and the frictional force was measured when moved at 3 cm / min. The friction coefficient was calculated from the frictional force. The indenter used had a contact surface diameter of 12 mm and was fitted with an artificial leather supplée on the surface that came into contact with the composite. The static and dynamic friction coefficients of the composite particles are preferably in the range of 0.4 or less, with both the static and dynamic friction coefficients being 0.01 to 0.40. The smaller the static and dynamic friction coefficients, the better the sliding properties. In particular, a value of 0.4 or less is preferred because it provides good smoothness and slipperiness. The coefficient of static friction is an indicator of the force required to start moving from a stationary state, and if it is high, you are more likely to feel sticking or creaking.
[0074] <Contact angle> The contact angle was measured as follows. A sample piece similar to that used in the friction coefficient measurement was prepared, a 10 μm water droplet was dropped onto it, and the contact angle after 0.3 seconds was measured using a contact angle meter, Model CA-D, manufactured by Kyowa Interface Science Co., Ltd. The preferred range for the amount of water repellent agent is one that results in a contact angle of 110° or more.
[0075] <Light diffusion intensity (light diffusion evaluation)> 5g of powder sample was added to 45g of clear lacquer and dispersed for 2 minutes at 3000 rpm using a disper mixer. The dispersion was dropped onto black carbon paper in a 2cm diameter circle and applied with a 5mil coater to form a coating. After air drying, the gloss was measured at three different points on the coating with a gloss meter and the average value was used. The lower the reflected light intensity at 85°, the more matte the finish and the better the light diffusion.
[0076] [Table 1]
[0077] [Table 2] A-1: Cellulose particles with an average particle size of 7 μm A-2: Cellulose particles with an average particle size of 15 μm A-3: Cellulose particles with an average particle size of 5 μm B-1: Methyltrimethoxysilane (KBM13, manufactured by Shin-Etsu Chemical Co., Ltd.) B-2: Silane resin powder (average particle size 5 μm, X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0078] [Example 7] Using the composite particles produced in Example 1, a foundation was prepared according to the formulation shown below. Foundation Ingredients Amount (%) (1) Cellulose-siloxane composite particles of Example 1 3.0 (2) Remaining amount of acrylic silicone-treated talc (Note 1) (3) Acrylic silicone treated sericite 10.0 (4) Metallic soap-treated mica 2.0 (5) Synthetic phlogopite 5.0 (6) Spherical silica powder 5.0 (7) Silicone-treated titanium dioxide microparticles 12.5 (8) Silicone-treated red iron oxide 0.6 (9) Silicone-treated yellow iron oxide 2.0 (10) Silicone-treated black iron oxide 0.2 (11) Silicone-treated titanium dioxide 6.0 (12) Diisostearyl Malate 2.0 (13) Glyceryl triisostearate 0.4 (14) Methylpolysiloxane 3.5 (15) UV absorber 5.0 (16) Preservatives (appropriate amount) (17) Flavoring (appropriate amount) (Note 1) NS Talc JA-46R-3F (manufactured by Kakuhachirinhaku Co., Ltd.)
[0079] [Examples 8 to 12, Comparative Examples 6 to 10] Foundations were prepared with the same formulation as in Example 7, except that the powder was replaced with the composite particles obtained in Examples 2 to 6 and Comparative Examples 1 to 5.
[0080] [Example 13] A foundation was prepared with the same composition as in Example 7, except that the amount of composite particles used in Example 7 was changed to 20%.
[0081] The foundation obtained above was subjected to the following evaluations, and the results are shown in Tables 3 and 4. [Tactile feel, smoothness] A use test was conducted by a panel of 20 experts, who evaluated the texture and smoothness of the cosmetic product based on the following criteria. The scores given by each panelist were then totaled and evaluated based on the following criteria. (Evaluation criteria) 5 points: Excellent 4 points: Excellent 3 points: Average 2 points: Inferior 1 point: Very poor (Evaluation criteria) ◎: Total score is 80 points or more ○: The total score is between 60 and 80 points △: The total score is between 40 and 60 points ×: The total score is less than 40 points
[0082] [Table 3]
[0083] [Table 4]
[0084] As shown in Table 4 above, foundations using surface-untreated cellulose particles or silane resin powder are inferior in feel and smoothness. Composite particles containing too little methyltrimethoxysilane relative to the cellulose particles result in foundations that are inferior in feel and smoothness. Furthermore, composite particles containing too much methyltrimethoxysilane relative to the cellulose particles tend to result in foundations that are inferior in smoothness. In contrast, as shown in Table 3 above, the cellulose-siloxane composite particles of the present invention provide foundations that are superior in feel and smoothness compared to surface-untreated cellulose particles.
[0085] When blended and used in cosmetics, the composite particles of the present invention can impart properties such as sliding properties, soft touch, and water repellency to the cosmetics, and can be blended in many cosmetics such as hair cosmetics, makeup cosmetics, sunscreens, etc. Furthermore, the composite powder of the present invention and cosmetics containing the composite powder can be expected to have biodegradable effects.
Claims
1. The composite particle is composed of a particle of cellulose or a cellulose derivative and a polyorganosilsesquioxane attached to the surface of the particle, and the polyorganosilsesquioxane is a polymer of an organotrialkoxysilane in an amount of 3 to 80 parts by mass per 100 parts by mass of the particle.
2. 2. The composite particle according to claim 1, wherein the cellulose or cellulose derivative particles have a volume average particle size of 1 to 300 μm.
3. 2. The composite particle of claim 1, wherein the organotrialkoxysilane is methyltrimethoxysilane.
4. A composite particle comprising a particle of cellulose or a cellulose derivative and a polyorganosilsesquioxane attached to the surface of the particle, wherein 30% or more of the surface area of the particle is covered with the polyorganosilsesquioxane.
5. The composite particles according to claim 4, wherein the particles of cellulose or a cellulose derivative have a volume average particle size of 1 to 300 μm.
6. 5. The composite particle according to claim 4, wherein the polyorganosilsesquioxane is a polymer of an organotrialkoxysilane.
7. The composite particle of claim 6 , wherein the organotrialkoxysilane is methyltrimethoxysilane.
8. A method for producing composite particles comprising (A) particles of cellulose or a cellulose derivative and a polyorganosilsesquioxane attached to the surfaces of the particles, the method comprising the steps of: subjecting 3 to 80 parts by mass of (B) an organotrialkoxysilane relative to 100 parts by mass of the (A) particles to a hydrolysis and condensation reaction in the presence of the (A) particles, water, and an alkali to form a polyorganosilsesquioxane; and attaching the polyorganosilsesquioxane to the surfaces of the (A) particles.
9. The method of claim 8 further comprising the step of removing water after said step.
10. A cosmetic comprising the composite particle according to any one of claims 1 to 7.
11. The cosmetic according to claim 10, comprising 1 to 50% by mass of the composite particles based on the total amount of the cosmetic.
12. The composite particle according to any one of claims 1 to 7, wherein a static friction coefficient of a composite containing the composite particle is 0.4 or less.